Analysis of rainwater quality in a quarry site in southwestern Nigeria - Taiwo, Temitope Mary; Ogunbode, Timothy Oyebamiji (Frontiers in Environmental Science, 2025)
IntroductionWater has been of paramount importance to humanity throughout history. Understanding the factors contributing to water pollution, particularly those that compromise its quality and sustainability, is essential. This study investigates the impact of quarry activities on the portability of rainwater within a quarry site, focusing on the relationship between quarry operations, heavy metals, and the physicochemical properties of rainwater.MethodsThe study was conducted at Sanlong Quarry Industry in Ifelodun, Southwestern Nigeria. Rainwater samples were collected along a 15–150 m transect within the quarry for analysis of heavy metals and physicochemical contents. Five heavy metals cadmium (Cd), chromium (Cr), zinc (Zn), lead (Pb), and magnesium (Mg) were determined using Atomic Absorption Spectrophotometer (AAS). Additionally, eight physicochemical properties, including electrical conductivity, pH, total solids, suspended solids, total dissolved solids, nitrate, turbidity, and total phosphorus, were analyzed using standard procedures. Variance and correlation analysis of the rainwater’s physicochemical parameters was conducted using Statistical Product for Service Solutions (SPSS).ResultsThe analysis indicated general compliance with water quality standards. However, elevated levels of Pb and Cd in certain areas exceeded WHO, NAFDAC, and US-EPA limits, while Cr, Zn, and Mg were found to have minimal impact on rainwater quality.DiscussionRainwater collected at Sanlong Quarry may not be safe for consumption due to heavy metal contamination, particularly Pb and Cd. This finding underscores the need for alternative clean water sources for both quarry staff and the surrounding community. Quarry management must prioritize the provision of clean water and raise awareness among personnel about the risks associated with consuming contaminated rainwater.